2012
DOI: 10.1115/1.4006399
|View full text |Cite
|
Sign up to set email alerts
|

Coal Ash Deposition on Nozzle Guide Vanes—Part II: Computational Modeling

Abstract: Coal ash deposition was numerically modeled on a GE-E3 high pressure turbine vane passage. A model was developed, in conjunction with FLUENT™ software, to track individual particles through the turbine passage. Two sticking models were used to predict the rates of deposition which were subsequently compared to experimental trends. The strengths and limitations of the two sticking models, the critical viscosity model and the critical velocity model, are discussed. The former model ties deposition exclusively to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…24 Therefore, actually, only the medium-sized particles are dominantly captured by the surface. This is confirmed by Barker et al, 23 who predicted higher capture efficiency for medium-sized particles using the critical velocity model. Field observations also show that ash deposit mass is primarily contributed by particles below 30 μm.…”
Section: ■ Discussionsupporting
confidence: 82%
“…24 Therefore, actually, only the medium-sized particles are dominantly captured by the surface. This is confirmed by Barker et al, 23 who predicted higher capture efficiency for medium-sized particles using the critical velocity model. Field observations also show that ash deposit mass is primarily contributed by particles below 30 μm.…”
Section: ■ Discussionsupporting
confidence: 82%
“…Owing to higher inertia, larger particles are directed towards the surface with high velocities in comparison to smaller particles [31]. Barker at al [35]. studied coal ash deposition on nozzle guide vanes numerically and validated their simulation results.…”
Section: Resultsmentioning
confidence: 92%
“…The study conducted in [22] utilized and compared both the critical viscosity model as well as the critical velocity model developed by El-Batsh and Haselbacher [14]. While both sticking models showed limitations, the critical viscosity model appeared to be more accurate for a larger range of particle size distributions, and was used in this study.…”
Section: B Critical Viscosity Modelmentioning
confidence: 98%
“…The deposition model is adapted from Barker et al [22], which is a derivative of the Tafti and Sreedharan critical viscosity model [16]. The model was compared to experimental results in Webb et al [23] which found that the model is accurate in predicting initial deposition rates but is not accurate after large-scale deposits are formed.…”
Section: Figure 1 -Volcanic Ash Deposition On Turbine Vanesmentioning
confidence: 99%
See 1 more Smart Citation